Efficacy and safety of traditional Chinese medicine for intracranial hemorrhage by promoting blood circulation and removing blood stasis: A systematic review and meta-analysis of randomized controlled trials - Lin, Wenjian; Hou, Jingjing; Han, Tianxiong; Zheng, Li; Liang, Huazheng; Zhou, Xiaoyu (Frontiers in Pharmacology, 2022)
Although blood-activating Chinese medicine (BACM) has been reported as an adjuvant therapy for intracranial hemorrhage (ICH) in China, high-quality evidence is still lacking. Our study aimed to collect the latest high-quality randomized controlled trials (RCTs) and evaluate the efficacy and safety of BACM for ICH. Fifteen RCTs, enrolling 1,579 participants, were included in our study. The pooled outcomes indicated that BACM combined with western medicine treatment (WMT) was superior to WMT alone for patients with ICH, demonstrated by the improvements in efficacy (RR=1.22 (95% CI, [1.13 to 1.32], p< 0.001), neurological functions (MDNIHSS = -2.75, 95% CI [- 3.74, -1.76], p< 0.001), activities of daily living (MDBarthel index = 5.95, 95% CI [3.92, 7.98], p< 0.001), cerebral hematoma and cerebral edema (MD cerebral hematoma = -2.94, 95% CI [-3.50, -2.37, p< 0.001 and MDcerebral edema = -2.66, 95% CI [-2.95, -2.37], p< 0.001), and the reductions in side effects and mortality (RR=0.84 (95% CI [0.60 to 1.19], p = 0.330 and RR=0.51 (95% CI, [0.16 to 1.65], p=0.260). In addition, three herbs (Conioselinum anthriscoides 'Chuanxiong' [Apiaceae], Camellia reticulata Lindl. [Theaceae], and Bupleurum sibiricum var. jeholense (Nakai) C.D.Chu [Apiaceae]) were the most commonly used in the treatment of ICH. Recently, there was a trend toward the extensive use of four other herbs (Rheum palmatum L. [Polygonaceae], Conioselinum anthriscoides 'Chuanxiong' [Apiaceae], Camellia reticulata Lindl. [Theaceae], Astragalus mongholicus Bunge [Fabaceae]) for ICH. We found BACM combined with WMT seems to be superior to WMT alone for patients with ICH.